Corak taburan spatial serta potensi allelopati Cuscuta campestris Yuncker di Semenanjung Malaysia / Muhammad Remy Othman - Othman, Muhammad Remy (2013)
Golden dodder (Cuscuta campestris Yuncker) is a problematic weed in abandoned, derelict, open and crop areas in Peninsular of Malaysia. In year 2009-2011, a research was conducted throughout the Peninsular of Malaysia. The objectives of the research are to list down the host of C. campestris, to identify the chemical compounds of active ingredients in C. campestris, to determine the allelopathy level of C. campestris, and to find out the types of protein that exist and the special features of C. campestris. The north part of Peninsular Malaysia had recorded 601.32 cm² of C. campestris population at 59 area involving 56 species of host followed by the East part of Peninsular Malaysia with dispersion of population at 92 area covering 118.32 cm2 involving 49 species and the Middle part of Peninsula Malaysia had recorded 3545.02 cm2 with 59 population area. Not more than 12 types of species of agricultural plant and 70 species of weed species become host of C. campestris. The species of Asystasia gangetica, Mikania micrantha, and Chromolaena odorata are the most common host found whereas C.campestris are usually inhibit cover crop (Calopogonium mucunoides and Pueraria phaseoloides), immature cassava, palm tree, and rubber tree. The TLC measurement and 1H NMR which had been conducted by combining the compounds of kaempferol are the main basis in C. campestris which produce the yellow colour of its stem. An extract from C. campestris is tested to determine the level of inhibition towards selected seeds and reveals that ethanol extract results in the effect of inhibition more than the other extract. SDS protein test reveal Pectin Methylesterase contained in C. campestris and its host was channelled by haustoria.